ASSESSMENT OF IMMUNOPATHOLOGICAL DEVELOPMENTS IN CHILDREN WITH NEPHROTIC SYNDROME WITH BACKGROUND PATHOLOGY (International Journal of Scientific Pediatrics, 2022)
In order to assess immunopathological changes in children with nephrotic syndrome with underlying pathology, 120 children aged 7 to 11 years were examined. Of these: group 1 - 35 children with NS (nephrotic form of CGN); group 2 - 35 children with NS against the background of LD; group 3 - 25 children with LD. Healthy group: 25 practically healthy children of the same age. It was determined that in children with nephrotic syndrome (nephrotic form of chronic glomerulonephritis) occurring with underlying pathology (lymphatic diathesis), specific clinical symptoms are characteristic, such as increased edema (100.0%), oliguria (100.0%), "chalky" pallor (74.2%), anasarca (9.0%) and hepatosplenomegaly (57.1%), in parallel with this, the development of severe anemia, a decrease in cortisol, an increase in lymphocytosis, proteinuria, fibrinogen, gamma globulin and cholesterol, contributing to the development of steroid-dependent and steroid-resistant forms of the disease. In nephrotic syndrome with lymphatic diathesis, a deficiency of the cellular link of immunity, a violation of the production of the cytokine IL-2, an increase in the content of ABL-kidneys, ABL-lungs, which remain preserved even in the period of remission of the disease, are characteristic, which confirm that in the treatment of such contingents of patients it is necessary to include in therapy adequate methods of immunocorrection.
Keywords: lymphatic diathesis; nephrotic syndrome; interleukin-2; immunitу